Education on Food, Fisheries and Agriculture - Anderson, Molly (Maine Policy Review, 2011)
This article describes the important role of education in helping the growing workforce in food-related industries, as well as the general population. The author notes that education in Maine about food, fisheries, and agriculture is provided in a wide variety of venues: formal degrees at colleges and universities; Cooperative Extension; farm-to-school programs; the Maine Organic Farmers and Gardeners Association (MOFGA); and even educational farms. A sidebar by John Rebar discusses the work of University of Maine Cooperative Extension.
Keywords: Maine; food system education; cooperative extension